2007
DOI: 10.1002/ibd.3780060204
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long- term follow-up of treatment for lymphocytic and collagenous colitis

Abstract: Summary:Collagenous colitis and lymphocytic colitis cause chronic watery diarrhea. Multiple therapies have been found to improve symptoms but there have been few long-term followup studies. Our goal was to obtain long-term clinical follow-up on a cohort of patients with independently confirmed typical histopathologic changes. Pathology slides from 32 cases of collagenous or lymphocytic colitis patients from 1988-1992 were independently reviewed. Twenty-five cases were confirmed by both groups of pathologist as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…In a follow-up study of CC, 63% of the patients had a lasting remission after 3.5 years, and in another cohort study, all 25 patients were improved 47 mo after diagnosis, and only 29% of them required ongoing medication [107,108] . A benign course was reported in 27 cases with LC, with resolution of diarrhea and normalization of histology in > 80% of patients within 38 mo [109] .…”
Section: Therapy and Prognosismentioning
confidence: 99%
“…In a follow-up study of CC, 63% of the patients had a lasting remission after 3.5 years, and in another cohort study, all 25 patients were improved 47 mo after diagnosis, and only 29% of them required ongoing medication [107,108] . A benign course was reported in 27 cases with LC, with resolution of diarrhea and normalization of histology in > 80% of patients within 38 mo [109] .…”
Section: Therapy and Prognosismentioning
confidence: 99%
“…Lymphocytic (LC) and collagenous (CC) colitis are two main subtypes of MC. They share many features, such as the clinical symptoms, association to autoimmune diseases and response to treatment [2,3]. Although they share some histological features they can be separated by histopathology [1].…”
Section: Introductionmentioning
confidence: 99%
“…In a follow-up study on CC conducted by Goff et al, 35 63% of patients remained in remission after 3.5 years. Meanwhile, in another cohort study conducted by Bonner et al, 36 all 25 patients showed improvement after 47 months of diagnosis, with 29% requiring continuous medication.…”
Section: 2mentioning
confidence: 91%